A contribuição do pluralismo metodológico no ensino de Ciências Naturais: Um estudo realizado com alunos de uma escola pública da Paraíba - Lustosa, Mariana Silva (2017)
The present work concerns research about the methodological pluralism as a teaching of the contents of the Natural Science, which we carried out with students from two 7 th grade classes from a public school in Lagoa Seca city (PB). In one of the classes the classes were taught with the methodological variation, in the other were taught classes with majority expository methodology. The data collection was based in note about of the intervention realized and in the application of two questionnaires to students. ( pretest- post test ) about the contents taught in the classes. Demonstrating a better performance of the students in the answer to the questionaries after didactic intervention, with games, conceptual maps, modeling and theater with puppets, in comparison to the results of the exclusively. Among the results obtained, we highlight that the interaction and the teaching strategies stimulated the attention of the students to the contents taught, providing the decrease of the dispersion. It was also possible to notice an increase in their motivation and their willingness to attend classes. The multiple activities developed based on methodological pluralism enabled the learning of concepts and attitudes that contributed significantly to the expansion of students cognitive abilities.